Childhood mouth-breathing consequences at adult age: ventilatory function and quality of life - Jovana de Moura Milanesi; Priscila Weber; Luana Cristina Berwig; Rodrigo Agne Ritzel; Ana Maria Toniolo da Silva; Eliane Castilhos Rodrigues Corrêa
Introduction Mouth breathing can affect the functions of the respiratory systems and quality of life. For this reason, children who grow up with this stimulus may have implications on physical and psychological aspects at adult age.Objective To evaluate childhood mouth-breathing consequences for the ventilatory function and quality of life at adult age.Materials and methods Prospective, observational and cross-sectional study with 24 adults, between 18 and 30 years old, mouth breathers during childhood, comprised the childhood mouth-breathing group (CMB). The childhood nasal-breathing (CNB) group was composed of 20 adults of the same age, without history of respiratory disease during all their lives. Measurements of maximal respiratory pressures, peak expiratory flow and 6-minute walk test were assessed. In addition, all the volunteers answered the Short Form-36 questionnaire (SF-36).Results The maximal inspiratory (p = 0.001) and expiratory (p = 0.000) pressures as well as the distance in the walk test (p = 0.003) were lower in the COB. The COB also presented lower score in the General Health domain of the SF-36 Questionnaire (p = 0.002).Conclusion Childhood mouth-breathing yields consequences for the ventilatory function at adult age, with lower respiratory muscle strength and functional exercise capacity. Conversely, the quality of life was little affected by the mouth breathing in this study.